Alteration in the endogenous intestinal flora of swiss webster mice by experimental Angiostrongylus costaricensis infection - Nobre, Vandack (2004)
Universidade Federal de Minas Gerais. Faculdade de Medicina. Departamento de Clínica Médica. Serviço de DIP. Belo Horizonte, MG, Brasil.